International business opportunity recognition and development. Issue 3 (19th November 2021) - Di Gregorio, Dante; Musteen, Martina Claasen; Thomas, Douglas
Abstract : Purpose: Understanding how international business opportunities (IBOs) are recognized and developed is critical to the study of international entrepreneurship. Design/methodology/approach: We draw on entrepreneurial cognition research broadly and the entrepreneurial judgment perspective specifically to develop a model of the recognition and development of IBOs by considering three theoretically important sets of drivers – social networks, international experience and a proactive mindset. We use a sample of 92 small- and medium-sized enterprises (SMEs) to test the model empirically. Findings: We find robust support. Entrepreneurial judgment surrounding IBOs and uncertain international business environments entails tapping social networks, international experience and a proactive mindset to both recognize third-person opportunities for someone as well as to act upon and develop IBOs as first-person opportunities from which a focal firm can profit. Originality/value: Conceptually and empirically, we peer inside the black box of IBO entrepreneurial judgment processes by jointly evaluating the abstract recognition of third-person opportunities as well as the concrete actions and interactions that develop the IBOs into first-person opportunities.